2012
DOI: 10.1073/pnas.1202786109
|View full text |Cite
|
Sign up to set email alerts
|

Azidoblebbistatin, a photoreactive myosin inhibitor

Abstract: Photoreactive compounds are important tools in life sciences that allow precisely timed covalent crosslinking of ligands and targets. Using a unique technique we have synthesized azidoblebbistatin, which is a derivative of blebbistatin, the most widely used myosin inhibitor. Without UV irradiation azidoblebbistatin exhibits identical inhibitory properties to those of blebbistatin. Using UV irradiation, azidoblebbistatin can be covalently crosslinked to myosin, which greatly enhances its in vitro and in vivo ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 31 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…Among those, para-nitroblebbistatin is the most latest described non-cytotoxic and photostable blebbistain derivative that displays the same inhibitory potency to myosins-2 as blebbistatin and allows studies of GFP-nonmuscle myosin-2 inhibition in live cells [204]. Another blebbistatin derivative, photoreactive azidoblebbistatin, covalently crosslinks to the myosin-2 motor domain after UV-irradiation [205]. This photoreactivity improves the in vitro and in vivo effectiveness when compared to blebbistatin but its binding to the myosin-2 motor domain is irreverible [205].…”
Section: Regulation By Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, para-nitroblebbistatin is the most latest described non-cytotoxic and photostable blebbistain derivative that displays the same inhibitory potency to myosins-2 as blebbistatin and allows studies of GFP-nonmuscle myosin-2 inhibition in live cells [204]. Another blebbistatin derivative, photoreactive azidoblebbistatin, covalently crosslinks to the myosin-2 motor domain after UV-irradiation [205]. This photoreactivity improves the in vitro and in vivo effectiveness when compared to blebbistatin but its binding to the myosin-2 motor domain is irreverible [205].…”
Section: Regulation By Small Moleculesmentioning
confidence: 99%
“…Another blebbistatin derivative, photoreactive azidoblebbistatin, covalently crosslinks to the myosin-2 motor domain after UV-irradiation [205]. This photoreactivity improves the in vitro and in vivo effectiveness when compared to blebbistatin but its binding to the myosin-2 motor domain is irreverible [205]. …”
Section: Regulation By Small Moleculesmentioning
confidence: 99%
“…[5] For in vivo applications of blebbistatin, optimization of its chemical structure is essential. Introduction of a nitro group at the C7 position (Scheme 1) of the tricyclic core of blebbistatin (7) led to slightly decreased fluorescence and increased photostability. [6] However, the biological application of this blebbistatin derivative was hampered by its strongly decreased binding constant and specificity to myosin II.…”
mentioning
confidence: 99%
“…[6] However, the biological application of this blebbistatin derivative was hampered by its strongly decreased binding constant and specificity to myosin II. Recently, we reported a highly myosin II-specific, photoinducible, C15-substituted azido derivative of blebbistatin, called para-azidoblebbistatin, [7] which forms covalent cross-links with its target proteins upon UV and bluelight irradiation. We observed that paraazidoblebbistatin-unlike blebbistatin-is nonfluorescent Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation